2022
DOI: 10.3390/ijms231911476
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Cervical Cancer by Fluorescence Lifetime Imaging Microscopy Combined with Unsupervised Machine Learning

Abstract: Cervical cancer has high morbidity and mortality rates, affecting hundreds of thousands of women worldwide and requiring more accurate screening for early intervention and follow-up treatment. Cytology is the current dominant clinical screening approach, and though it has been used for decades, it has unsatisfactory sensitivity and specificity. In this work, fluorescence lifetime imaging microscopy (FLIM) was used for the imaging of exfoliated cervical cells in which an endogenous coenzyme involved in metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Fluorescence lifetime imaging microscopy (FLIM) was used to analyze NAD(P)H in exfoliated cervical cells from healthy volunteers and patients with different degrees of cancerization. The results showed that cancer cells have a relatively short average fluorescence lifetime and less protein-bound NAD(P)H ratio and are more prone to glycolysis than OXPHOS compared with normal cells [ 106 ]. Chen et al [ 107 ] identified 293 NAD + metabolic-related genes and 21 prognostic NAD + metabolic-related genes in 39 CC patients: ADAMTS10, ANGPTL5, APCDD1L, CCDC85A, CGREF1, CHRDL2, CRP, DENND5B, EFS, FGF8, P4HA3, PCDH20, PCDHAC2, RASGRF2, S100P, SLC19A3, SLC6A14, TESC, TFPI, TNMD, ZNF229 , and for the first time described SLC19A3 as a prognostic signature through NAD + metabolism, providing clinical prognostic biomarkers and therapeutic targets for CC.…”
Section: Effects Of Nad + and Its Precursors On Re...mentioning
confidence: 99%
“…Fluorescence lifetime imaging microscopy (FLIM) was used to analyze NAD(P)H in exfoliated cervical cells from healthy volunteers and patients with different degrees of cancerization. The results showed that cancer cells have a relatively short average fluorescence lifetime and less protein-bound NAD(P)H ratio and are more prone to glycolysis than OXPHOS compared with normal cells [ 106 ]. Chen et al [ 107 ] identified 293 NAD + metabolic-related genes and 21 prognostic NAD + metabolic-related genes in 39 CC patients: ADAMTS10, ANGPTL5, APCDD1L, CCDC85A, CGREF1, CHRDL2, CRP, DENND5B, EFS, FGF8, P4HA3, PCDH20, PCDHAC2, RASGRF2, S100P, SLC19A3, SLC6A14, TESC, TFPI, TNMD, ZNF229 , and for the first time described SLC19A3 as a prognostic signature through NAD + metabolism, providing clinical prognostic biomarkers and therapeutic targets for CC.…”
Section: Effects Of Nad + and Its Precursors On Re...mentioning
confidence: 99%
“…36 Ji et al combined FLIM with ML algorithms for imaging of exfoliated cervical cell samples that helps in predicting risk of cervical cancer in the patients with a sensitivity and specificity of 90.9% and 100%, respectively. 37 Wang et al used phasor analysis for the image analysis obtained from FLIM that helps in distinguishing normal, low, and, high grade cervical lesions based on the relationship between metabolic changes and cancer development. 38 Qiu et al performed a strong near-infrared absorption based fluorescence imaging for the early diagnosis of cervical cancer.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…Ji et al. combined FLIM with ML algorithms for imaging of exfoliated cervical cell samples that helps in predicting risk of cervical cancer in the patients with a sensitivity and specificity of 90.9% and 100%, respectively 37 . Wang et al.…”
Section: Optical Modalities For Cervical Cancer Detectionmentioning
confidence: 99%
“…Furthermore, cervical cancer [66], skin cancer [67,68], oral cancer [69,70], esophageal squamous cell carcinoma and adenocarcinoma of the esophagogastric junction [71] can also be detected and distinguished early using AI models. The above studies greatly demonstrate the potential of AI models in detecting early cancers.…”
Section: Tumor Screening and Early Detectionmentioning
confidence: 99%